2015
DOI: 10.1007/s11292-015-9247-6
|View full text |Cite
|
Sign up to set email alerts
|

Twelve experiments in restorative justice: the Jerry Lee program of randomized trials of restorative justice conferences

Abstract: Objectives We conducted and measured outcomes from the Jerry Lee Program of 12 randomized trials over two decades in Australia and the United Kingdom (UK), testing an identical method of restorative justice taught by the same trainers to hundreds of police officers and others who delivered it to 2231 offenders and 1179 victims in 1995- J Exp Criminol (2015) 11:501-540 DOI 10.1007 2004. The article provides a review of the scientific progress and policy effects of the program, as described in 75 publications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 37 publications
2
80
1
Order By: Relevance
“…Participants assigned to RJ reported feeling safer and had less fear of revenge after participating in VOCs (Beven et al 2005;Davis 2009). Further, improvements in hyperarousal displayed longevity, as anxiety of revictimisation was lower in victims who had received RJ compared with those whose cases had been adjudicated by the courts up to 10 years after receiving the intervention (Sherman et al, 2015b). Consistent with these findings, symptoms of irritability and aggression were significantly different between justice interventions.…”
Section: Arousal and Reactivity Symptomssupporting
confidence: 54%
See 2 more Smart Citations
“…Participants assigned to RJ reported feeling safer and had less fear of revenge after participating in VOCs (Beven et al 2005;Davis 2009). Further, improvements in hyperarousal displayed longevity, as anxiety of revictimisation was lower in victims who had received RJ compared with those whose cases had been adjudicated by the courts up to 10 years after receiving the intervention (Sherman et al, 2015b). Consistent with these findings, symptoms of irritability and aggression were significantly different between justice interventions.…”
Section: Arousal and Reactivity Symptomssupporting
confidence: 54%
“…In adult victims, it was consistently evidenced that anger was lower in the RJ group compared with the group receiving the customary justice intervention (Beven et al 2005;Davis 2009;Gal and Moyal 2011). Further, reductions in anger were found to hold up to 10 years following the intervention (Sherman et al 2015b). RJ also supported improvements in mood and cognition in an adolescent sample.…”
Section: Negative Alterations In Mood and Cognition Symptomsmentioning
confidence: 86%
See 1 more Smart Citation
“…As in multicentered treatment research in medicine, these primary studies should be designed as a series of replications to test the reproducibility of findings (e.g., in a meta-analysis). The evaluation of a restorative justice program by Sherman et al (2015) is a good example of this strategy.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…A systematic review concluded that restorative justice is a promising approach for both adults and youth (76). However, restorative justice may reduce rates of recidivism only for more serious juvenile crimes and not for misdemeanors or offenses such as drunk driving (128). It should be noted that most evaluations did not include true randomization, and the program’s voluntary nature may introduce selection bias that presents an obstacle to obtaining reliable estimates of program effects because offenders may refuse to participate in the programs (76).…”
Section: Interventions That Workmentioning
confidence: 99%